Safety evaluation of the food enzyme carboxypeptidase C from the genetically modified Aspergillus niger strain PEG - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme carboxypeptidase C (EC 3.4.16.5) is produced with the genetically modified Aspergillus niger strain PEG by DSM Food Specialties B.V. The genetic modifications do not give rise to safety concerns. The food enzyme is free from viable cells of the production organism and its DNA. It is intended to be used in nine food manufacturing processes. Dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 2.053 mg TOS/kg body weight (bw) per day in European populations. The toxicity studies were carried out with a xylanase obtained from A. niger strain XEA. The Panel considered this food enzyme as a suitable substitute for the carboxypeptidase to be used in the toxicological studies, because both strains were derived from the same recipient strain, the location of the inserts was comparable, no partial inserts were present and the production methods were essentially the same. Genotoxicity tests did not raise a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1850 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 901. A homology search for the amino acid sequence of the food enzyme to known allergens was made and one match with a wheat allergen was found. The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, especially in wheat‐allergic individuals, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.